DEVELOPMENT OF SOFT SKILLS LEARNING MODELS THROUGH COOPERATIVE LEARNING IN LEARNING HEALTH AND SPORTS PHYSICAL EDUCATION IN BASIC SCHOOL - Richi Afriansyah; Sukirno Sukirno; Iyakrus Iyakrus (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to: 1) determine the development of learning models of students' soft skills that are implemented through cooperative learning in HSPEL learning in elementary schools; 2) knowing the effectiveness of the ability of students in the implementation of the development of learning models of soft skills through cooperative learning in HSPEL learning in elementary schools. Research and development procedures are carried out through three stages of Borg & Gall's ten research and development steps, namely: (1) preliminary research (needs analysis), (2) development of learning models, (3) testing and evaluation of models. The resulting data are expert validation data, small group trial data, large group test data and student learning outcomes. Data analysis used during development is a qualitative descriptive analysis. The results of the development of this soft skills learning model fall into a good category so it is suitable for use. This is based on expert validation which obtained a percentage of 78.67%. Data collected from results; (1) small-scale trials on students showed 70% results, and observations showed 73.33%. (2) large-scale trials on students showed 80% results, and observations showed 80% results. (3) learning outcomes data that get 80% results. Based on the results of these studies it can be concluded that the development of soft skills through cooperative learning learning models is effectively used in elementary schools.